Σχεδιασμός παραβολικού συλλέκτη για παραγωγή θερμότητας σε βιομηχανίες - Κτίστης, Παναγιώτης (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The use of solar energy to meet energy necessities is the most widespread form of Renewable Energy Source. While it was proven that a very large percentage of the global energy consumption is used by industries that are using medium temperatures (120°C - 250°C), manufacturers do not seem to prefer solar systems to meet their thermal needs. On the contrary, in addition to the given environmental contamination, they remain dependent on the fluctuation of the fuel price, which directly affects the final cost of the product. At the same time, several researchers have suggested the use of small-scale parabolic tough collectors as an ideal solution, but the industries do not adopt this technology. Initially, the study looked at why this technology did not find the expected response. Furthermore, the cost of thermal energy production were studied in order to design a collector that meets the requirements of industries that have a genuine need to find a solution. The overall scope of the research is to design a small-scale parabolic collector with low manufacturing and operating costs in order to be evaluated in a production system. The parabolic collector has a rim angle of 90°, a width of 1.5m and a length of 3m. No vacuum conditions are maintained in the absorber, with the outer receiving and glass diameter being 35mm and 73mm respectively. For a required temperature of 150οC, a very good yield curve is observed, with a collector overall efficiency of 71.9%. To conclude with, once the collector is applied to a solar system, its contribution to production is assessed. After economic analysis and optimization is estimated that seven parabolic collectors can cover 73.4% of the total dairy industry thermal needs (615MJ per day) as presented in an extreme scenario, depreciation of the expenditures of the whole system could be achieved in the 4th year of operation.
Keywords: Parabolic trough collector; Industrial process heat; Παραβολικός συλλέκτης; Παραγωγή θερμότητας σε βιομηχανία